Ipazia, eroina tragica o vittima melò? Un viaggio estetico nel mito letterario dell’alessandrina (Itinera, 2012)
If it is true that ancient historical sources about Hypatia are terribly run out, the same cannot be said for modern literature and narrative sources that dealt with her story and created a veritable literary legend that will be shortly rebuilt in this essay. Special attention will be devoted to the possible and varied meanings of the story of the ancient philosopher, to its many interpretations and to the different aesthetic universes of reference involved in its narrative. The final remarks will claim that the contributions of previous authors, rather than return the face of Hypatia, tend to offer a mirror through which the reader actually gazes at his society, his subjectivity and his cultural history.